Prenatal Alcohol Exposure and Sleep Alterations in Children: A Systematic Review - Jiménez Guerrero, Alba (My University, 2025)
This systematic review had the purpose of summarize the current knowledge on sleep alterations in children with prenatal alcohol exposure (PAE). A literature search was performed using Scopus and Web Of Science (WOS), using the following equations: (1) Sleep AND Prenatal alcohol exposure children and (2) Sleep AND Fetal alcohol exposure. Of the 216 articles, 14 were retrieved for inclusion in this review. The studies were gathered by the main technique used: actigraphy (n= 5), electroencephalography (n= 2), video (n= 2), polysomnography (n= 3) and other methods (n= 2). Children and infants that were prenatally exposed to alcohol were reported to have disturbed sleep through the manifestation of low sleep efficiency, sleep fragmentation, shorter sleep duration, altered respiratory indices, hypermotor events (mini foot movements, foot rubbing, limb movements and scratching) and affected melatonin production. Most studies (n= 13) identified this difference among controls and PAE/Fetal Alcohol Spectrum Disorder (FASD) sample, but just one (Hanft et al., 2006) reported different results, highlighting that there was no difference between groups (PAE vs. control) in quiet sleep (QS%) and active sleep (AS%) at any age across the first year of life. Results showed that children that has been prenatally exposed to alcohol struggle with sleep alterations, and that these alterations can even appear when the mother’s alcohol consumption is low but continuous: the volume is not important per se but rather the absence or presence of alcohol.

Esta revisión sistemática tiene el propósito de resumir el conocimiento actual que se tiene sobre las alteraciones del sueño en niños expuestos prenatalmente al alcohol (PAE). Se hizo una búsqueda de literatura usando Scopus y Web Of Science (WOS) con las siguientes ecuaciones: (1) Sleep AND Prenatal alcohol exposure children and (2) Sleep AND Fetal alcohol exposure. De 216 artículos, 14 se escogieron para esta revisión. Los estudios se agruparon según su principal técnica usada: actigrafía (n= 5), electroencefalografía (n= 2), video (n= 2), polisomnografía (n= 3) y otros métodos (n= 2). Niños y bebés con PAE reportaron tener un sueño alterado, manifestado a través de una baja eficacia, fragmentación del sueño y duración reducida del sueño, índices respiratorios alterados, eventos hipermotores (movimientos y roce de pies, movimiento de extremidades y rascado) y una producción de melatonina afectada. La mayoría de los estudios (n= 13) señalaron esta diferencia entre grupos controles y la muestra expuesta prenatalmente al alcohol o con trastorno del espectro, pero solo uno (Hanft et al., 2006) presentó resultados diferentes, resaltando la nula diferencia entre los grupos (PAE vs. control) en sueño tranquilo (QS%) y sueño activo (AS%) durante el primer año de vida. Esta revisión sistemática muestra cómo los niños expuestos prenatalmente al alcohol tienen alteraciones en el sueño, y que estas aparecen incluso cuando la madre tiene un bajo pero continuo consumo: el volumen no es importante per se, si no la ausencia o presencia del alcohol.
Exposición prenatal al alcohol y alteraciones del sueño en niños: Una revisión sistemática
Keywords: Síndrome alcohólico fetal; Sueño - Trastornos; Alcoholismo en el embarazo; Sueño; Niños; Psicología - Trabajos fin de grado; Fetal alcohol spectrum disorder; Prenatal alcohol exposure; Neurobehavioural disorder associated with prenatal alcohol exposure; Neurodevelopmental disorders; Sleep; Children; Sleep disorder; Trastorno del espectro alcohólico fetal; Exposición Penatal al alcohol; Trastorno neuroconductual asociado con la exposición prenatal al alcohol; Trastornos del neurodesarrollo; Sueño; Niños; Trastorno del sueño